KARAKTERISTIK BATUBARA DAERAH KATANJUNG DAN SEKITARNYA : CHARACTERISTICS OF COAL IN THE KATANJUNG AREA - Tanggara, Deddy Nan Setya Putra; Kristiana, Wita (JURUSAN TEKNIK PERTAMBANGAN UPR, 2023)
Kapuas Regency is an area in Central Kalimantan Province which has natural resource potential in the form of various mining materials, including coal. This study aims to determine the characteristics of coal found in Kapuas Regency, in Katanjung area. The research method used in this research is calculating and comparing the results of coal testing with the standard classification. Laboratory analysis results on coal samples showed a total moisture content of 9.66%, volatile matter component of 35.23%, calorific value of 6980, ash of 14% and solid carbon of 48.66%. To determine the coal rank in the study area, the average calorie value of coal 6,908 was converted and compared with the ASTM Standard coal classification. Based on the result, the coal in the study area can be categorized as High Volatile C Bituminous Coal. Coal in the study area has high calories and has the potential to be use, both as thermal coal and as a mixture of PCI coal or Pulverized coal injection. PCI coal is coal used in the steelmaking process for injection of pulverized coal into blast furnaces used in combination with coke. The use of PCI allows steelmakers to reduce the amount of coke needed in the steelmaking process. Keywords: Coal, Katanjung, Kapuas, PCI